2020
DOI: 10.1587/nolta.11.206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of generalized class-E rectifier

Abstract: This paper presents a semi-analytical expression of the generalized class-E rectifier. Effect of low output-filter inductance is included in the theoretical formula presented in this paper. The harmonic components are considered in the current flowing through the outputfilter inductance. For obtaining the theoretical waveforms, the coefficients of each frequency component are obtained by numerical calculations. By using the semi-analytical expression, characteristics of the class-E rectifier can be comprehende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Additionally, N = 5 is adopted in the investigations. We confirmed that N = 5 is sufficiently large to derive the accurate waveforms [3]. Figure 6 shows the maximum value of the power output capability c pmax and ωL 2 /R to obtain c pmax for fixed ωL f /R as a function of ωC D R. For drawing this figure, the ωL f /R is fixed firstly.…”
Section: Performance Investigationsupporting
confidence: 53%
See 3 more Smart Citations
“…Additionally, N = 5 is adopted in the investigations. We confirmed that N = 5 is sufficiently large to derive the accurate waveforms [3]. Figure 6 shows the maximum value of the power output capability c pmax and ωL 2 /R to obtain c pmax for fixed ωL f /R as a function of ωC D R. For drawing this figure, the ωL f /R is fixed firstly.…”
Section: Performance Investigationsupporting
confidence: 53%
“…Therefore, the current i f has a sufficiently small ripple, which can be ignored. A sizable current ripple, however, appears in case of the low Q of the output filter, as shown in Fig 2. The rectifier design is more flexible by considering any Q of the output filter as a design parameter [3], [11]. There is, however, no investigation of the class E/F n rectifier at any Q of output filter until now.…”
Section: Class E/f N Rectifiermentioning
confidence: 99%
See 2 more Smart Citations
“…The resonant rectifiers are suitable for high-frequency and high-efficiency operations due to the soft switching. The class-E rectifier [7,8] is one of the typical resonant rectifiers. The rectifier has a single diode which largely reduces the conduction loss compared to the other types of resonant rectifiers.…”
Section: Introductionmentioning
confidence: 99%